PENINGKATAN PRODUKTIVITAS BENANG POLYESTER COTTON 45 MELALUI ANALISIS TOTAL QUALITY CONTROL (Studi kasus di PT Panca Bintang Tunggal Sejahtera) - Afifah Alrizqi; Yuciana Wilandari; Abdul Hoyyi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
PT Panca Bintang Tunggal Sejahtera is a company which operate in textill and garment. The main product is polyester cotton 45 yarn. In the production activity, still failed product. To determine what factors caused the failure of polyester cotton 45 yarn, used the analysis of Total Quality Control to control devices such as check sheet, stratification, bar chart, control chart, cause and effect diagrams, Pareto charts, and scatter plot. From the results of the check sheet, stratification and histogram obtained the highest type of failure is uneven sliver, which is as much as 1871 kg for a month. From the individual unit control chart, indicated that the activities of the production process there are deviations which are beyond the limits of product controllers that need improvement. A cause and effect diagram result show that the biggest factor causing the failure of the product due to labor factor due to lack of training and supervision. Therefore, the company can make improvements with priority on the labor factor.